Loss of Advocates' Immunity Rights Due to Violations of Professional Ethics in the Case of Razman Arif Nasution - April Naufal Anggraeni; Aldi Darmawan; Ismi Rusyanti (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The right to immunity for advocates is an important instrument to ensure that advocates can practice their profession freely, especially in defending clients' interests in court, without being disturbed by legal threats. However, this right is not absolute and can be lost if the advocate violates the code of ethics or harms the dignity of the court, as in the case of Razman Arif Nasution, which raised questions about the balance between professional protection and ethical responsibility. This paper aims to examine the limits of the right to immunity for advocates in the context of violations of professional ethics, as well as explore its legal implications for the disciplinary mechanisms of advocate organizations. The method used is normative juridical, with a statute approach and a case study approach. The study findings indicate that advocate protection must still be linked to compliance with professional ethics, so that in practice disciplinary mechanisms have a strategic role in upholding professionalism.